Directory Enabled Smart Spaces - Cahill, Enda (Trinity College Dublin. Department of Computer Science, 2002)
Significant research and development in the area of system management has been carried out over the last number of years. This research has led to a number of proven technologies that are currently being used to manage large-scale systems. This dissertation aims to build upon this research and development to examine how a smart space management system could be created. The dissertation examines how an existing information model can be extended to adequately model the information that is required to manage a smart space. Policies, which can control the behaviour of the smart space, are also modelled using existing policy models. The information model and the policies are then mapped onto a directory service that is used as a repository. A prototype application is described which can use the directory service to control and manipulate a smart space. This prototype application is used as a platform to demonstrate the design decisions that have been taken. Conclusions will be drawn as to the potential benefits of using the Directory Enabled Networks Initiative and the Common Information model for the representation of smart space management information. The suitability of using policy based management techniques in the management of a smart space environment will also be discussed.
Keywords: Computer Science